2014
DOI: 10.1080/10942912.2013.791835
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Temperature Influence on the Rheological Behaviour of Honeys

Abstract: 15The purpose of this work was to examine the viscoelastic properties of Spanish honeys with Newtonian behaviour, presenting a highly viscous part (loss modulus was much greater than the 20 elastic modulus). The loss modulus (G'') and viscosity increased with moisture content and a 21 decrease with temperature. Exponential and power law models were applied to fit loss modulus 22 and viscosity data. Polynomial models were proposed to describe the combined effect of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…Validation on a set of Spanish honey samples having 32-42% fructose, 24-35% glucose, 79-83% reducing sugars, 16-19% water, and 3.4% sucrose demonstrated a Newtonian behaviour of all samples [45]. The loss modulus, G″, and viscosity show increase with moisture content, and decrease with temperature.…”
Section: Rheological Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation on a set of Spanish honey samples having 32-42% fructose, 24-35% glucose, 79-83% reducing sugars, 16-19% water, and 3.4% sucrose demonstrated a Newtonian behaviour of all samples [45]. The loss modulus, G″, and viscosity show increase with moisture content, and decrease with temperature.…”
Section: Rheological Behaviourmentioning
confidence: 99%
“…It has been concluded that crystallization is significantly affected by the botanic origin, temperature profile, and storage time. Modelling of the viscoelastic properties and their relation to moisture, palynological spectrum, and sugars have been addressed by several groups, using either domestic or European honey for study [44][45][46][47][48]. The declared objectives were correct prediction of the rheological behaviour and identification of further correlation with the botanical origin.…”
Section: Rheological Behaviourmentioning
confidence: 99%
“…Two-way analysis of variance was carried out to determine the effects of concentration and temperature on the viscosity of bitter orange juice concentrate using SPSS statistics software version 18.0 (SPSS Inc., Chicago, IL, USA). The mean relative percentage deviation modulus (D) was calculated for the deviance of observed value from the calculated value (Equation (3)) (Oroian et al, 2014):…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the effects of temperature and concentration on the flow properties are essential for understanding unit operations such as heat transfer and evaporation (Altan & Maskan, 2005;Oroian et al, 2014;Ozkanli & Tekin, 2008;Rao, Cooley, & Vitali, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The rheological properties of honey revealed a Newtonian behaviour in the great part of the articles published (Oroian 2012;Oroian 2013, Kayacier & Karaman 2008Ramzi et al 2015), but in some case have been reported as a non-Newtonian fluid (Witczak et al 2011, Yanniotis et al 2006Ahmed et al 2007). In the last decade, the influences of different factors on honey rheological parameters have been investigated, as: temperature (Yanniotis et al 2006), chemical composition (Oroian et al 2014), shear rate and water content (Al-Mahasneh et al 2013).…”
Section: Introductionmentioning
confidence: 99%